Expression changes of microRNAs in menstrual blood samples of different menstrual cycle collection days. (December 2017) - Li, Zhilong; Peng, Duo; Tian, Huan; Wang, Jijun; Xia, Yu; Zhang, Lin; Bai, Peng
Abstract: Three microRNAs (miR-141-3p, miR-497-5p, miR-143-5p) have been screened out and confirmed to be promising markers to distinguish between menstrual blood and peripheral blood by our previous study. However, studies reported the expression levels of miRNAs might be different in menstrual blood samples of different menstrual cycle collection days. To evaluate the dynamic changes of expression levels of these three miRNAs in menstrual blood samples from different menstrual cycle collection days, 51 menstrual blood (day 1–5 of menstrual cycle) samples were collected and detected. Total RNA was extracted then corresponding cDNA was prepared and three TaqMan Assays were run in triplicate using the TaqMan Universal PCR Master Mix II without UNG (Life Technologies, USA). Bioinformatics analysis was used to search target genes of three miRNAs attempting to explain the results. After comparing with the expression levels of previous peripheral blood samples, we found that miR-141-3p and miR-497-5p were still reliable markers to distinguish menstrual blood from peripheral blood after the sample size was enlarged.